Radiolabeled dendritic probes as tools for high in vivo tumor targeting: application to melanoma1. Issue 12 (28th March 2015) - Parat, Audrey; Kryza, David; Degoul, Françoise; Taleb, Jacqueline; Viallard, Claire; Janier, Marc; Garofalo, Antonio; Bonazza, Pauline; Heinrich-Balard, Laurence; Cohen, Richard; Miot-Noirault, Elisabeth; Chezal, Jean-Michel; et al.
<x xml:space="preserve">Abstract</x> A small-sized and bifunctional 111In-radiolabeled dendron shows high in vivo targeting efficiency towards an intracellular target in a murine melanoma model.